A snug little flock : the social origins of the Riel Resistance, 1869-70 - Pannekoek, Frits (Watson and Dwyer, 1991)
Questions about the identities of the mixed-blood Indian-European peoples of Canada and the United States have puzzled historians and anthropologists in both countries. Who are the mixedbloods of North America? Why do they have a strong collective identity in Canada, and virtually none in the United States? Why is the collective identity in Canada largely French-Cree and Catholic? What happened to the English-speaking Protestant Halfbreeds? Why do the Protestant, English-speaking mixed-bloods no longer exist as a unique group either in Canada or in the United States, but identify themselves as White, Indian or Metis in Canada and Indian or White in the United States? While it has become commonplace to view mixed-blood peoples as products of the culture and economy of the fur trade, it is much more difficult to trace the roots of the process that created an identifiable Metis 'nation'. It is even more difficult to determine why no strong mixed-blood identity emerged in the United States. The Manitoba Arts Council; Social Science Federation of Canada; Social Sciences and Humanities Research Council of Canada